2012
DOI: 10.1118/1.4764563
|View full text |Cite
|
Sign up to set email alerts
|

Fast transit portal dosimetry using density‐scaled layer modeling of aSi‐based electronic portal imaging device and Monte Carlo method

Abstract: The layer model of EPID built for Monte Carlo calculations offered fast (less than 1 min) and accurate calculation for transit dosimety and dose reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…On another front, a number of groups have modeled the response of the EPID for dosimetric purposes using Monte Carlo techniques 16 , 17 . One group, in particular, was able to calculate accurate 2D dose maps inside a phantom by means of sophisticated EPID modeling 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…On another front, a number of groups have modeled the response of the EPID for dosimetric purposes using Monte Carlo techniques 16 , 17 . One group, in particular, was able to calculate accurate 2D dose maps inside a phantom by means of sophisticated EPID modeling 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Our calculational EPID model was determined to be accurate within 2% from EPID measurement. 28 This difference affected dose reconstruction accuracy because our algorithm utilizes calculated EPID response. The dose reconstruction algorithm itself is as accurate as forward MC calculation at beam axis (i.e., flat dose region), as it utilizes MC calculated responses.…”
Section: Iiia Reconstruction Methods Validationmentioning
confidence: 99%
“…27 After the image calibration, the dose calibration of EPID images was performed, creating a dose calibration matrix between the measured image of the flat flood field to the corresponding calculated dose image using the EPID model described in our other study. 28 After the calibration, the test beam was irradiated on the 10-cm thick homogeneous phantom [ Fig. 2(a)] and EPID that was placed at 150 cm.…”
Section: Iic2 Measurementsmentioning
confidence: 99%
“…In our prior study, we have developed and successfully demonstrated a method of dose reconstruction. [2][3][4] In this study, our objectives are (1) to develop a system of clinical application of reconstructed dose (above mentioned) that includes dose registration between fractions of treatment and dose-volume-histogram generation and (2) to demonstrate it on a deformable prostate phantom.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] It assumes that the anatomical information (i.e. computer tomography or CT) of a patient under treatment is available and reconstructs "delivered" dose to such information from "transit" dose recorded in EPID.…”
Section: Introductionmentioning
confidence: 99%